MODEL OF DEVELOPMENT OF INFORMATION-COMMUNICATIVE COMPETENCE OF FUTURE PRIMARY CLASS TEACHERS (Scientific journal of the Fergana State University, 2023)
In this article, the model of information-communicative competence development of future primary school teachers is considered. Formation of mathematical competence is of great importance today. The ability to use mathematical knowledge to describe and explain surrounding events and phenomena serves as one of the requirements of the State Education Standard starting from primary education.